2021
DOI: 10.3389/fpubh.2021.730150
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning Approach to Predict Survival Outcomes Using Wearable Actigraphy Device Among End-Stage Cancer Patients

Abstract: Survival prediction is highly valued in end-of-life care clinical practice, and patient performance status evaluation stands as a predominant component in survival prognostication. While current performance status evaluation tools are limited to their subjective nature, the advent of wearable technology enables continual recordings of patients' activity and has the potential to measure performance status objectively. We hypothesize that wristband actigraphy monitoring devices can predict in-hospital death of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…The results of our current study are in line with our previous related study results, including two prospective observational studies [ 28 , 29 ] and a scoping review [ 44 ]. One of our previous findings showed that the majority of the included studies in the scoping review, which utilized wrist-worn wearable devices in cancer populations, focused on physical activity, sleep analysis, and heart vital signs and showed a positive correlation between patient-reported and wearable outcomes [ 44 ], while in the other study, automatic survival prediction using an LSTM DL model showed feasibility in clinical settings and possible benefits in end-of-life care settings without healthcare professionals [ 29 ]. Additionally, in the third study, wearable devices reported greater angle and spin movements as early as within the first 48 h of observation in the cancer patients who were still alive after discharge from the hospice inpatient unit [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of our current study are in line with our previous related study results, including two prospective observational studies [ 28 , 29 ] and a scoping review [ 44 ]. One of our previous findings showed that the majority of the included studies in the scoping review, which utilized wrist-worn wearable devices in cancer populations, focused on physical activity, sleep analysis, and heart vital signs and showed a positive correlation between patient-reported and wearable outcomes [ 44 ], while in the other study, automatic survival prediction using an LSTM DL model showed feasibility in clinical settings and possible benefits in end-of-life care settings without healthcare professionals [ 29 ]. Additionally, in the third study, wearable devices reported greater angle and spin movements as early as within the first 48 h of observation in the cancer patients who were still alive after discharge from the hospice inpatient unit [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…The validated cutoff values for the KPS and PPI were 50% and 6.0, respectively [ 29 ]. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), overall accuracy, and the area under the receiver operating characteristic (AUROC) curve were used to evaluate the predictive accuracy of the KPS and PPI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies in Table 1 and approximately half of all studies included in total focused on predicting mortality as a clinical outcome, which includes predicting short-term mortality risk 14▪,15,18▪,24▪ and survival over a longer horizon 19–21,22▪▪,23▪▪,25,29. Mortality risk and survival time were both usually predicted using machine learning (ML) models that analyze various patient factors such as clinical parameters, changes during treatment, and symptoms 14▪,15,18▪,20,21,22▪▪,23▪▪,24▪,25. The accuracy of ML and deep learning (DL) models is typically evaluated by their area under the curve (AUC) value, which measures the accuracy of predictions and a model’s discriminative ability where 1.0 represents the highest possible AUC score indicating perfect discrimination 11,39.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of ML and deep learning (DL) models is typically evaluated by their area under the curve (AUC) value, which measures the accuracy of predictions and a model’s discriminative ability where 1.0 represents the highest possible AUC score indicating perfect discrimination 11,39. The models in Table 1 had AUC values between 0.70 and 0.92 indicating generally good model performance 14▪,15,18▪,19–21,23▪▪,24▪,25,26,40. Interestingly, models predicting 60-day and especially 180-day mortality had lower AUC values compared to 30-day mortality models 19,20,24▪,40, suggesting that predicting acute mortality risk could be more reliable than prediction over a longer term.…”
Section: Discussionmentioning
confidence: 99%